Solitary cylindroma with malignant transformation - Cherry Bansal; Mayanka Batra; Nirupma Lal; A N Srivastava; Mayanka Batra; Nirupma Lal; A N Srivastava (Wolters Kluwer Medknow Publications, 2012)
A 59-year-old woman presented with a history of rapidly progressive recurrent tumor of 6.5 cm diameter of the scalp. Histopathological examination revealed a case of malignant cylindroma. There has been no recurrence or metastases and the patient is disease free at the end of 15 months postoperatively. Malignant transformation occurs less often in solitary form of cylindroma, but once transformed, tumors behave aggressively with extensive local infiltrative growth or metastases. The case is reported to document a rare case of malignant cylindroma arising in a patient with solitary cylindroma on the parieto-temporal region.